2021
DOI: 10.3390/s21062176
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Bathroom Activities in Older Adults Using Wearable Sensors: A Systematic Review and Recommendations

Abstract: This article provides a systematic review of studies on recognising bathroom activities in older adults using wearable sensors. Bathroom activities are an important part of Activities of Daily Living (ADL). The performance on ADL activities is used to predict the ability of older adults to live independently. This paper aims to provide an overview of the studied bathroom activities, the wearable sensors used, different applied methodologies and the tested activity recognition techniques. Six databases were scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Most studies found that technologies were not mature enough to detect activity changes or improve independence [ 88 , 89 , 92 , 105 ]. For monitoring older adults in general, % (3/N) of studies noted weak evidence for detecting changes in ADLs [ 82 - 84 ], and 2 studies showed improved QoL [ 85 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies found that technologies were not mature enough to detect activity changes or improve independence [ 88 , 89 , 92 , 105 ]. For monitoring older adults in general, % (3/N) of studies noted weak evidence for detecting changes in ADLs [ 82 - 84 ], and 2 studies showed improved QoL [ 85 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, these technological methods for HAR have been applied frequently in homes [ 6 ], their bathrooms being precisely one of the spaces whose activities have been monitored on several occasions [ [7] , [8] , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the detection and monitoring of these activities has been the object of study using technologies such as sound capture [ 7 , 8 ], images or infrared [ 9 ], wearable accelerometer [ 10 ], wearable sensors [ 11 ], among others. In these cases, although quite interesting results have been achieved, there are limitations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations